Evaluation of the corrective effect of modified laparoscopic longitudinal gastric resection practice on existing metabolic changes in morbidly obese patients - Muradov Alijon Salimovich; Teshaev Oktyabr Ruhullaevich; Mavlanev Alimbay (Zien Journals, 2024)
To study the corrective effect of laparoscopic longitudinal gastric resection (LLGR) on obesityrelated metabolic disorders in morbidly obese patients. This scientific work is based on the results of a comprehensive examination and treatment of 187 patients treated for morbid obesity in our clinical bases from 2021 to 2023. Analysis of comorbidities in the compared groups showed that 64% of the comparison groups had metabolic disorders. The majority of these patients were patients with 3rd degree of obesity. Positive changes in lipidogram analysis were observed in patients after LOBR procedure. Also, when hemostasis indicators were studied, convincing positive changes were observed in the 1st and 3rd stages of coagulation hemostasis. In patients with chronic obesity, our recommended modification of LOBR increased cardio esophageal and gastric stapler line strength, eliminating the 2.2% stapler line failure observed in our control group in our main cohort. It also led to a reduction in gastroesophageal reflux disease symptoms from 14% to 6.1%. In conclusion, these pathological changes are closely related to obesity, and the elimination of obesity led to the elimination of these metabolic disturbances
Keywords: metabolic syndrome; morbid obesity; bariatric surgery; concomitant diseases